ASSESSING KNOWLEDGE MANAGEMENT READINESS TO IMPROVE DATA QUALITY BY PREVENT INCORRECT DATA INPUT ON ERP SYSTEM IN COMPONENT REBUILD CENTER PT KALCOAL - Budiman, Firman
To fulfil the demand of availability component for supporting the mining operation at PT Kalcoal. Recondition component daily activity of recondition is entanglement from one process to another until the end of process. For transform digitalization, recondition component activity will using Enterprise Resource Planning (ERP) in every process.